Juvenile systemic lupus erythematosus complicated with posterior reversible encephalopathy syndrome: a case report and literature review - Man Luo (Orphanet Journal of Rare Diseases, 2025)
Abstract Background Posterior reversible encephalopathy syndrome (PRES) is an acute or subacute neurological syndrome with clinical manifestations including headache, vision loss, altered mental status, and seizures. Magnetic resonance imaging(MRI) can assist in clarifying the diagnosis. Systemic lupus erythematosus (SLE) is an autoimmune disease, and the occurrence of PRES is infrequent, especially in children with SLE. Case description Our patient was initially diagnosed with juvenile systemic lupus erythematosus involving the skin, joints, and kidneys. The patient was treated with glucocorticoids and cyclophosphamide, which led to a partial improvement in symptoms. However, the patient experienced neurological symptoms and elevated blood pressure, and head MRI revealed swelling and diffuse damage to the bilateral occipital parietal gyrus. The patient was diagnosed with PRES. Results The symptoms were relieved after actively lowering blood pressure, dehydrating with mannitol, and treating with glucocorticoids, cyclophosphamide, and telitacicept. Six months later, no abnormalities were observed in the follow-up head MR image. We searched PubMed to review the characteristics of 15 children with SLE who developed PRES, and most of them recovered after active treatment. Conclusion Various factors can lead to complications of PRES in paediatric patients with systemic lupus erythematosus. In our patient, the likely cause was the high disease activity of SLE. This review revealed that juvenile SLE cases accompanied by PRES are often associated with lupus nephritis, hypertension, and high disease activity. Most patients recover with timely and active treatment, with only a few experiencing recurrence.